IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING FAST HANDS GAME AT THE SECOND GRADE STUDENTS OF SMPN 1 BAROMBONG - Sinta Dewi Anggung; Nur Ima (IICLS (Indonesian Institute for Corporate Learning and Studies), 2023)
This research aimed at finding out the improvement of students’ vocabulary mastery by using Fast Hands Game. This research used a pre-experimental method. The population of this research was the second grade students of SMPN 1 Barombong. The total sample was 26 students and it used a purposive sampling technique. In collecting data, the researcher used vocabulary test that is administered of pre-test and post-test. The result of this research showed that the mean score in post-test was higher than the mean score in pre-test (80,54 > 46,73). The result of t-test was greater than the t-table value (13,38 > 2,060) at the significance level of 0,05. Based on the result of data analysis, it is concluded that using Fast Hands Game can improve the students’ vocabulary mastery at SMPN 1 Barombong.